Appendagitis following Diagnostic Laparoscopy and Laparoscopic Appendicectomy. (4th July 2016) - Kumar, R.; Bamford, R. F.; Kumar, D.; Singh-Ranger, G.
Abstract : Appendagitis is an uncommon clinical entity, often not recognised, and mistaken for more serious infective conditions. We describe a proven case of appendagitis which occurred after confirmed appendicitis. We postulate that this condition can coexist with appendicitis and indeed may be the result of coinflammation. This has several implications. Firstly, clinicians must retain an index of suspicion for this condition in a patient with localised abdominal pain which occurs after appendicitis. Secondly, it would be reasonable to suggest careful examination of colocated appendages in a patient with an otherwise normal-appearing appendix. Treatment might require laparoscopic resection, as performed in this case.